Optimal Income Taxation For Transfer Payments Under Different Social Welfare Criteria - Helpman, Robert Cooter Elhanan (Quarterly Journal of Economics, 1974)
l. INTRODUCTIO NEfficiency principles are no guide to optimal tax rates when income redistributio n is the purpose of that taxation.Optimal tax rates for redistributio n must be obtained through maximizatio n of a social welfare function constrained by technology and by what Pigou called the "announcem ent effects" of the tax."Announcem ent effects" refer to the alterations in the economic behavior of individuals induced by the tax scheme, which appear as constraints upon collective choice because they arise from individual utility-maxi mizing behavior that society cannot or will not inhibit.When redistribution is accomplishe d through lump sum transfers, announceme nt effects are assumed to be nil, and the problem of the distribution branch of government 1 -equating everyone's marginal social utility of incomeis transparent.Mirrlees 2 has attempted an analytic solution for the optimal income tax by maximizing a utilitarian social welfare function constrained to allow for the incentive effects of the tax upon work effort.Phelps 3 and Sheshinski 4 repeated this calculation for the Rawls social welfare function, and Fair 5 did a similar analysis for a social welfare function written as the product of individual utilities.This article develops a simulation technique for calculating the optimal income tax under any social welfare